OFFLINE REKSO RELEASE 6 CAT AND ENCARTA ENCYCLOPEDIA AS A TOOL IN TRANSLATION TEACHING - Budiarto Budiarto (Journal of English Language and Literature (JELL), 2018)
The present study is to focus on the use of Offline Rekso Release 6 CAT (Computer Aided Translation (CAT) systems) and Encarta Encyclopedia software as a tool in translation teaching. It is true that students have to apply their theory through translation process by making use of dictionaries. However, both translation theory and dictionaries are still not enough to accelerate the translation process, even when they can derive meaning from context. This study is based on a brief theoretical literature overview, classroom activities and observation. The findings suggest that offline Rekso release 6 CAT and encyclopedia software are a tool that can help translation teaching.